2007
DOI: 10.1177/1744987107077532
|View full text |Cite
|
Sign up to set email alerts
|

The self-directed learning readiness of first year bachelor of nursing students

Abstract: Self-directed learning (SDL) has evolved as a method of learning into Australian nurse education over the past few years with enthusiastic claims of increasing student numbers and access to learning. It is an educational concept and transformative learning process that has been used increasingly in adult education, especially within tertiary institutions. Most tertiary educational institutions now offer components of their nursing programmes using self-directed learning methods that may include distance progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 7 publications
8
51
1
4
Order By: Relevance
“…These scales were developed by Guglielmino in 1977 8 and Fisher in 2001 5 and have been used to study self-directed learning in medical, nursing, pharmacy, and non-medical education. [9][10][11][12][13] Fisher established construct validity and internal consistency through a pilot study of undergraduate nursing students. 5,14 Content validity for both scales was determined using Delphi surveys.…”
Section: Introductionmentioning
confidence: 99%
“…These scales were developed by Guglielmino in 1977 8 and Fisher in 2001 5 and have been used to study self-directed learning in medical, nursing, pharmacy, and non-medical education. [9][10][11][12][13] Fisher established construct validity and internal consistency through a pilot study of undergraduate nursing students. 5,14 Content validity for both scales was determined using Delphi surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Fisher et al's version of the SDLRS and adaptations of it have been widely used within pre-registration nurse education in Australia (Smedley, 2007;Phillips et al 2015); Italy (Cadorin et al, 2013;Cadorin et al 2015); the UK (Williamson, 2007);and China (Bin Yuan et al, 2012). Smedley's (2007) quantitative study found that first year nursing students have a limited ability to self-manage their learning with some lacking the ability to manage time; selfdiscipline; plan learning; set times for learning; apply methodical and systematic approaches to learning; problem solve; prioritise and seek out information. Smedley recommended that lecturers develop and implement strategies to improve students' skills of self-directedness.…”
Section: Resultsmentioning
confidence: 99%
“…The coming together of unprepared students in the educational process is a source of student anxiety [6,43] and by extension, an impetus for unsafe clinical practices [4] . Sanctioned unpreparedness may negatively affect self-directed learning and meta-cognitive processes involved in the transition of novice student to nurse [44,45] .…”
Section: Discussionmentioning
confidence: 99%